Water Vapor Adsorption Capacity of Thermally Fluorinated Carbon Molecular Sieves for CO2 Capture. (25th September 2013) - Jung, Jin-Young; Yu, Hye-Ryeon; In, Se Jin; Choi, Young Chul; Lee, Young-Seak
Abstract : The surfaces of carbon molecular sieves (CMSs) were thermally fluorinated to adsorb water vapor. The fluorination of the CMSs was performed at various temperatures (100, 200, 300, and 400°C) to investigate the effects of the fluorine gas (F2 ) content on the surface properties. Fluorine-related functional groups formed were effectively generated on the surface of the CMSs via thermal fluorination process, and the total pore volume and specific surface area of the pores in the CMSs increased during the thermal fluorination process, especially those with diameters ≤ 8 Å. The water vapor adsorption capacity of the thermally fluorinated CMSs increased compared with the as-received CMSs, which is attributable to the increased specific surface area and to the semicovalent bonds of the C–F groups.